An Integrative Review: Work Environment Factors Associated With Physical Activity Among White-Collar Workers. (February 2014) - Lin, Yun-Ping; McCullagh, Marjorie C.; Kao, Tsui-Sui; Larson, Janet L.
The purpose of this review is to synthesize the research evidence for the role of the work environment—workplace physical activity policies and resources and job strain factors—in explaining physical activity in white-collar workers. White-collar workers are at risk for developing a sedentary lifestyle, which contributes to all-cause mortality. Understanding how work environment can influence worker physical activity is important for the development of effective interventions. We reviewed 15 research articles that describe the relationship between work environment factors and physical activity in predominantly white-collar workers. Relatively consistent evidence was found for the effects of supportive workplace policies and resources. Weak evidence was found for the effects of job strain. Both work environment factors have the potential to influence physical activity but require further exploration to fully understand their contribution to physical activity in white-collar workers. Limitations and implications are discussed.